The range of applicability of models for the flow of high concentration backfill slurries in pipelines - Goosen, Peter Edward (Department of Civil Engineering, 2016)
Two models recently developed at the University of Cape Town are intended to model the flow of high concentration backfill slurries. These models are the Cooke model for dense phase flow of cyclone classified tailings and the Paterson model for stabilised flow of high concentration full plant tailings. These two materials (cyclone classified tailings and full plant tailings) form the extremes, in terms of particle size distribution, of tailings materials used as backfill in South African gold mines. The purpose of this dissertation is to investigate the possibility of applying these models in the region, in terms of particle size distribution, between full plant tailings and cyclone classified tailings. Measured pressure gradient data has been collected for materials with particle size distributions ranging from full plant tailings to cyclone classified tailings. The calculated model predictions are then compared with the measured data in order to determine the range of applicability of the models. Three intermediate materials were made up by mixing full plant tailings and cyclone classified tailings in ratios of 1 to 2, 1 to 1 and 2 to 1. These, together with the cyclone classified tailings and two full plant tailings materials, provided the range of materials in terms of particle size distribution. The six materials are characterised in terms of relevant solid and particle properties. Measured pressure gradient data is then presented covering two pipe diameters (40 mm and 80 mm nominal bore), a range of solids concentrations (35% to 52% by volume) and a range of flow velocities (0.5 to 4.5 m/s). The models of Cooke and Paterson are reviewed. Model predictions are then calculated for comparison with the measured data. The range, in terms of solids concentration and particle size distribution, over which each model is in acceptable agreement with the measured data is then presented and reported as the range of applicability of the model.